2008
DOI: 10.1109/ted.2008.916717
|View full text |Cite
|
Sign up to set email alerts
|

Gallium–Indium–Zinc-Oxide-Based Thin-Film Transistors: Influence of the Source/Drain Material

Abstract: Abstract-During the last years, oxide semiconductors have shown that they will have a key role in the future of electronics. In fact, several research groups have already presented working devices with remarkable electrical and optical properties based on these materials, mainly thin-film transistors (TFTs). Most of these TFTs use indium-tin oxide (ITO) as the material for source/drain electrodes. This paper focuses on the investigation of different materials to replace ITO in inverted-staggered TFTs based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(96 citation statements)
references
References 20 publications
(24 reference statements)
2
92
1
1
Order By: Relevance
“…TFT is comparable and in some cases superior to those of a-GIZO TFTs that have been proved to build up quite large area active matrix with excellent performances, when compared with today's technology [33,78]. This is a clear advantage since the replacement of In by Sn in the Ga-Zn-O system, is quite important due to the limited availability of In.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFT is comparable and in some cases superior to those of a-GIZO TFTs that have been proved to build up quite large area active matrix with excellent performances, when compared with today's technology [33,78]. This is a clear advantage since the replacement of In by Sn in the Ga-Zn-O system, is quite important due to the limited availability of In.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays these active oxides are key components in a wide range of device applications like sensors [29] and thin-film transistors (TFTs), where it has been demonstrated that they can present high electronic performance even when disordered ionic oxides are used [30][31][32][33][34][35][36]. Concerning p-type oxide semiconductors, this activity has been also pursued in the last years [37][38][39][40][41][42][43][44][45].…”
mentioning
confidence: 99%
“…최근에 이러한 한계를 극복하고자 소자 특성 및 신 뢰성 향상에 대한 연구가 활발히 진행되고 있다 [6][7][8][9][10][11][12]. 다양한 물질의 조합을 통한 특성 향상뿐만 아 니라 [6,7] [ ] …”
Section: 서 론 1)unclassified
“…Particularly, amorphous indium zinc oxide (a-IZO) was used for an S/D electrode of ZnO TTFTs due to its high transparency and lower resistivity. Although there was a lot of research regarding S/D electrodes of ZnO based TFTs, such as the transparency, resistivity, and contact problem with the channel layer, the relation between the stability of ZnO based TFTs under the various stress and S/D electrodes is still unknown [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%